2018
DOI: 10.1590/1983-21252018v31n203rc
|View full text |Cite
|
Sign up to set email alerts
|

Soil Chemical Attributes and Corn Productivity Grown on Legume Stubble in Agroforestry Systems

Abstract: Leguminous species can improve nutrient cycling and chemical quality of Oxisols, resulting in higher productivity of intercropped crops. Thus, this research aimed to evaluate the decomposition rate and nutrient accumulation in legume stubble, as well as its contribution to soil chemical attributes, the growth of baru trees (Dipteryx alata Vogel), and yield of intercropped maize in an agroforestry system. The experiment was developed during the crop years of 2010-2011 and 2011-2012, in Goiás State, Brazil. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…In addition to the C/N ratio, lignin, polyphenol and chemical composition are factors that affect the decomposition rate in cover crops (Lima Filho et al 2014). These characteristics along with the stage of development at desiccation time (Padovan et al, 2015) and the climatic conditions during the evaluated period (Collier et al, 2018) show the ability of each species to maintain the cover on the soil.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the C/N ratio, lignin, polyphenol and chemical composition are factors that affect the decomposition rate in cover crops (Lima Filho et al 2014). These characteristics along with the stage of development at desiccation time (Padovan et al, 2015) and the climatic conditions during the evaluated period (Collier et al, 2018) show the ability of each species to maintain the cover on the soil.…”
Section: Resultsmentioning
confidence: 99%
“…The lower production of DM of the signal grass is probably related to the fact that the plant has a longer vegetative cycle than the SH and PM (Collier et al, 2018), which was evident when managed, SH and PM were in full bloom, while the SG was still at the beginning of flowering.…”
Section: Resultsmentioning
confidence: 99%
“…In the harvest of 2008/09 and 2009/10, Pacheco et al (2013) observed T½ life of 42 (165%) and 111 (435%) days for brachiaria, 63 (223%) and 108 (382%) days for millet, and 44 (113%) and 130 (334%) days for brachiaria + pigeonpea, respectively. Collier et al (2018) observed T½ life of 57 (245%) days for sunn hemp when it was cultivated for 170 days. These results prove that the residue decomposition from the cover crops evaluated are decreased and present great T½ life on soil, when compared to the results observed in the irrigated area of this study.…”
Section: Discussmentioning
confidence: 95%
“…This great rate of decomposition of the brachiaria residues can be justified by the low temperature variation and elevated humidity conditions that occurred during this period of the year, in addition to the daily irrigation for vegetable production, which accelerates the decomposition process, as evidenced by Torres et al (2015), Assis et al (2016), Pacheco et al (2017), andCollier et al (2018).…”
Section: Discussmentioning
confidence: 97%